2013
DOI: 10.1128/jvi.02820-12
|View full text |Cite
|
Sign up to set email alerts
|

2G12-Expressing B Cell Lines May Aid in HIV Carbohydrate Vaccine Design Strategies

Abstract: The highly conserved cluster of high-mannose glycans on the HIV-1 envelope glycoprotein, gp120, has been highlighted as a target for neutralizing antibodies. 2G12, the first HIV-1 antiglycan neutralizing antibody described, binds with an unusual domainexchanged structure that creates a high-affinity multivalent binding surface. It is an interesting challenge for rational vaccine design to generate immunogens capable of eliciting domain-exchanged 2G12-like responses. We recently showed that di-mannose recogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
(54 reference statements)
0
13
0
Order By: Relevance
“…Although most germline antibody-Env interactions have focused on anti-CD4-BS antibodies, a few studies examined similar interactions between Env and bNMAbs that recognize epitopes outside the CD4-BS. Doores et al reported that the germline form of bnMAb 2G12 (a carbohydrate-binding antibody derived from VH3-21) does not recognize Env (35). In contrast, Bonsignori et al examined the interaction of CH01 to CH04, antibodies that recognize a complex epitope involving elements of the second and third variable regions (V2 and V3 loops) of the gp120 subunit, including an N-linked glycan at position 160, and reported that a very limited number of Envs bind the predicted germline form of this Ab (14).…”
mentioning
confidence: 99%
“…Although most germline antibody-Env interactions have focused on anti-CD4-BS antibodies, a few studies examined similar interactions between Env and bNMAbs that recognize epitopes outside the CD4-BS. Doores et al reported that the germline form of bnMAb 2G12 (a carbohydrate-binding antibody derived from VH3-21) does not recognize Env (35). In contrast, Bonsignori et al examined the interaction of CH01 to CH04, antibodies that recognize a complex epitope involving elements of the second and third variable regions (V2 and V3 loops) of the gp120 subunit, including an N-linked glycan at position 160, and reported that a very limited number of Envs bind the predicted germline form of this Ab (14).…”
mentioning
confidence: 99%
“…Effective immunogens must, therefore, be capable of engaging the B cell receptor (i.e., the gl-bnAb), before affinity maturation of the bnAb in the germinal centers. However, this process is hampered by the low affinity of gl-bnAbs to Env, often due to their inability to accommodate conserved N-linked glycans ( Doores et al., 2013 , Hoot et al., 2013 , Ma et al., 2011 , McGuire et al., 2014 , Xiao et al., 2009 ). Thus an alternative, albeit closely linked, approach to eliciting bnAbs, is to prime with glycan-depleted immunogens capable of engaging gl-bnAbs, and subsequently boost with their “filled-in” derivatives to drive the development of neutralization breadth ( Jardine et al., 2013 , McGuire et al., 2013 , Medina-Ramirez et al., 2017 , Stamatatos et al., 2017 , Steichen et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 11 Of note is the structural resemblance of the α-(1 → 2)-linked oligomannose part to the D1 arm of mammalian high-mannose glycans, which are particularly abundant on HIV-1 gp120. 12 Rhizobium radiobacter Rv3 LOS and heat-killed cells are bound by the oligomannose-specific HIV-neutralizing antibody 2G12 and a crystal structure of the carbohydrate backbone of Rhizobium radiobacter strain Rv3 complexed to the 2G12 antibody has recently been determined. 13 In order to further exploit the natural mimicry of high-mannose carbohydrate epitopes of HIV-1 gp120 seen with this bacterial LOS scaffold, we have set out to extend the bacterial oligosaccharides in order to elicit HIV neutralizing antibodies.…”
Section: Introductionmentioning
confidence: 99%